Addition of docetaxel, zoledronic acid, or both to first-line long-term hormone therapy in prostate cancer (STAMPEDE): survival results from an adaptive, multiarm, multistage, platform randomised controlled trial - John Wagstaff (The Lancet, 2015)
In this multi arm multi stage designed trial 2962 men with hormone sensitive prostate cancer were randomised to one of four arms. The control arm consisted of either surgical or chemical castration alone (standard of care (SOC)). In all other arms patients received either surgical or chemical castration plus docetaxel (Doc) alone, zoledronic acid (ZA) alone or Doc plus ZA. 1817 (61%) men had metastatic (M)+ disease, 448 (15%) had nodal (N)+/X M0, and 697 (24%) had N0M0. Median overall survival was 71 months for SOC alone, not reached for SOC+ZA (p=0.45), 81 months for SOC+Doc (p=0.006) & 76 months for SOC+Doc+ZA (0.022). Grade 3–5 adverse events were reported for 399 (32%) patients receiving SOC, 197 (32%) receiving SOC+ZA, 288 (52%) receiving SOC+Doc, and 269 (52%) receiving SOC + ZA + Doc. ZA showed no evidence of survival benefit and should not be part of SOC. Doc showed a significant improvement in overall survival and should become SOC for suitably fit men with prostate cancer starting long term hormone therapy.